Reproductive Aspects of Banana Prawn (Fenneropenaeus Merguiensis) For Recommendations of The South Sorong MPA Zone - Dhani, Arya Kusuma; Marsan, Ehdra Beta; Kembaren, Duranta D; Mansur, Mr.; Rotinsulu, Christovel (JFMR (Journal of Fisheries and Marine Research), 2020)
Reproduction aspects of banana prawn were important in determining of the fisheries management. These results can indicate the condition of fisheries that are or will be managed. Banana prawn was one of the main commodities in South Sorong fisheries. This study aims to estimate some of the reproductive aspects ofÂ Fenneropenaeus merguiensisÂ as part of a management measure to determining the zone to be a no-take zone area in the prospective area of South Sorong MPAs. The data analyzed were from data collecting from January to December 2018 in three sampling sites in South Sorong, among others Inanwatan, Bakoi, and Konda with the results of 5,009 carapace length samples, 4,589 including sex observation and 3,621 including banana prawn GMS observations. Data analysis performed by analyzing the distribution of carapace length frequency, sex ratio, length-weight relationship, length at first maturity (Lm50), and length at first captured (Lc50). The results of this analysis showed that the ratio between male and female gender was not balanced, with male gender to be less with a ratio of 0.4: 1.4 overall in NTZ 2 and 3. Comparison of Lc and Lm in NTZ 2 and NTZ 3 were respectively Lc < Lm and Lc > Lm. More fishing pressure will have implications to reduce the average size of banana prawn caught. Overall, NTZ 3 had relatively more stable conditions compared to NTZ 2.